Cooperative Script as A Strategy in Optimizing Listening Learning Outcomes of SMA Negeri 1 Mandastana Students - Muhammad Nazaruddin (FKIP ULM, 2023)
This classroom action research aims to determine how effective the cooperative script learning model is in improving students' listening skills in class XI.IPS.2 at SMA Negeri 1 Mandastana. The research participants were 36 students, and the study was conducted in two cycles. Each cycle included two face-to-face meetings. The data for this study were acquired utilizing observation sheet instruments, learning accomplishment exams, and student responses to the cooperative script learning model. The data was then analyzed descriptively and qualitatively. The study's findings indicated that using the cooperative script model enhances learning outcomes and student activities in listening learning. Prior to using this learning model, the class average was 59.43. Following the implementation of this model, actions 1 and 2 cycles I increased to 65.43 and 70.29, respectively. Meanwhile, the class average in action 1 cycle 2 increased to 75.14. According to the student replies, 93% of students enjoyed and felt assisted by this learning paradigm, while just 7% did not feel helped. The study's implications include that the cooperative script learning model can be employed as an alternative to maximize learning outcomes and student activities in listening learning. This learning technique can also boost students' learning reactions and make them more interested in the teaching and learning process. As a result, teachers might think about adopting cooperative script learning models to create effective and efficient learning techniques.